2008
DOI: 10.1260/174795408785024207
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Physical Tests, Measures, and Clubhead Speed in Elite Golfers

Abstract: The purpose of this study was to investigate the relationship between selected physical tests and clubhead speed, and whether body mass should be considered when presenting the test results. Thirty-three male elite golfers (estimated skill range: Hcp +5 to 0, age 18–30 years) participated in the study. The following test categories were measured and compared to clubhead speed with Pearson r correlation: vertical jumps (squat jump, counter movement jump, and counter movement jumps with arm swing); body mass str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 7 publications
3
54
1
Order By: Relevance
“…The current study reported high reliability in the range of field tests used and statistical significance with CHS in all performance measures apart from LLCMJ. By comparison, lower levels of reliability have been reported in previous work (37) and a range of other studies assessing physical relationships with CHS did not report reliability statistics for the physical performance tests (15,19). The medicine ball rotational throw used in the current study displayed high reliability (ICC = 0.90) and this is comparable to other work using the same test (14).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…The current study reported high reliability in the range of field tests used and statistical significance with CHS in all performance measures apart from LLCMJ. By comparison, lower levels of reliability have been reported in previous work (37) and a range of other studies assessing physical relationships with CHS did not report reliability statistics for the physical performance tests (15,19). The medicine ball rotational throw used in the current study displayed high reliability (ICC = 0.90) and this is comparable to other work using the same test (14).…”
Section: Resultscontrasting
confidence: 61%
“…Subjects performed a standardized warm up including dynamic stretching and five practice shots. Subsequently, three recorded drives were completed separated by 60 second rest periods with instructions to swing maximally as has been suggested previously (15). The highest of the three swing speed values was used to report club head speed values.…”
Section: Golf Drive Performancementioning
confidence: 99%
“…3) climbing and gymnastics, 4) combat sports, and 5) strength disciplines. INSERT TABLE 3 ABOUT HERE INSERT TABLE ABOUT (3,16,50,62,73,74,86,96,101,103,117,134,137,172,173,176,192,193,197). A comparison of professional baseball players revealed trivial and moderate non-significant HGS differences between the Major League Baseball (MLB©) and minor league baseball ("AAA" and "AA") players, respectively; whereas, moderate and large significant differences were observed between MLB players in comparison to "A" and rookie league players, respectively (76).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Due to this important interaction between the ground and the golfer, a number of studies have sought to determine the mechanisms associated with performance enhancement within the game of golf. Specifically, field-based investigations have highlighted significant relationships between CHV and vertical jump peak power (r = 0.61, p < 0.01) (21), (r = 0.54, p < 0.01) (36), jump height (r = 0.47, p < 0.01) (21), (r = 0.44, p < 0.05) (36), and repetition maximum strength during a back squat (r = 0.54, p < 0.01) (21), (r = 0.81, p < 0.05) (34). Whilst these relationships advocate the use of field-based protocols, without laboratory equipment, such as force plates, these protocols are unable to ascertain more in-depth performance strategies such as vertical ground reaction forces (vGRF).…”
Section: Introductionmentioning
confidence: 99%